The Conversion of the Adopted Children’s Clan in the Village of Tumbak from the Islamic Law Point of View - Misbahul Munir Makka; Rezki AS Albatati; Faradila Hasan; Sakinah Putri Alting (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
This study aims to see the process of conversing the clan of adopted children by the community in Tumbak Village Posumaen District and the reasons they adopt children and to analyze them in terms of Islamic law. This research method is field research in Tumbak Village using interview analysis to the actors of the clan conversion and their biological parents. The results of the study revealed that parents conversed their clan after adopting a child to make the adopted child feel like their biological child and, most of the local people adopted a child because the couple had no children. However, in this incident, it turned out that there was a change in the name or surname of the adopted children since the adoptive parents intent to make them feel truly like biological offspring. Islam considers this a wrong affair. Even though the child is being cared for by adoptive parents, they are still not allowed to forget the biological parents, because this will have an impact on the inheritance and guardianship matters of the adopted child.